2017
DOI: 10.1182/blood-2016-12-757823
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic origin of Langerhans cell histiocytosis and Erdheim-Chester disease in adults

Abstract: Langerhans cell histiocytosis (LCH) and Erdheim-Chester disease (ECD) are rare histiocytic disorders induced by somatic mutation of MAPK pathway genes. BRAF V600E mutation is the most common mutation in both conditions and also occurs in the hematopoietic neoplasm hairy cell leukemia (HCL). It is not known if adult LCH or ECD arises from hematopoietic stem cells (HSCs), nor which potential blood borne precursors lead to the formation of histiocytic lesions. In this study, BRAF V600E allele-specific polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
143
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 39 publications
1
143
0
3
Order By: Relevance
“…[176][177][178] Myeloid cDC2, however, rapidly up-regulate langerin to high levels and form Birbeck granules with GM-CSF or TSLP and TGF-b or BMP7. 133,134,179 In vivo evidence for these two pathways has recently been reported in the homeostasis of mucosal LC 164 but direct evidence is lacking in humans.…”
Section: Developmentmentioning
confidence: 99%
“…[176][177][178] Myeloid cDC2, however, rapidly up-regulate langerin to high levels and form Birbeck granules with GM-CSF or TSLP and TGF-b or BMP7. 133,134,179 In vivo evidence for these two pathways has recently been reported in the homeostasis of mucosal LC 164 but direct evidence is lacking in humans.…”
Section: Developmentmentioning
confidence: 99%
“…BRAF ‐V600E has been shown to be present in hematopoietic stem cells and myeloid progenitors in the bone marrow of high‐risk LCH patients. Additionally, CD1c+ dendritic cells have been shown to acquire high CD1a and CD207 expression with granulocyte‐macrophage colony‐stimulating factor and transforming growth factor‐beta alone in vitro . In contrast, classical CD14+ monocytes required additional notch ligation.…”
Section: The Cell Of Originmentioning
confidence: 99%
“…35 Berres et al 13 and transforming growth factor-beta alone in vitro. 36 In contrast, 37 Constitutive activation of the MAPK pathway due to BRAF mutation plays a critical role in LCH. A previous study identified BRAF-V600E in CD34+ cells in patients with hairy cell leukemia.…”
Section: The Cell Of Ori G Inmentioning
confidence: 99%
“…12 Additionally, two recent studies highlighted that the cell of origin of one third of patients with systemic histiocytosis resides in CD34 + hematopoietic progenitor cells prior to committed monocytes/macrophages. 13,14 Two main biologic mechanisms might explain the link between CMML and ECD. The first one would be a differentiation from a clonal CMML cell into foamy…”
mentioning
confidence: 99%